Players Unleashed ! Modding The Sims and the Culture of Gaming - Sihvonen, Tanja (MediaMatters, 2011)
The author of this hugely informative study explores the question of what happens when players practise and negotiate computer code, various ideologies, and the game itself by modding (modifying a game) in the context of The Sims, the bestselling computer game of all time. Sihvonen examines the technical and material specificities of The Sims mods, as well as their cultural context. Viewed as a manifestation of participatory culture, modding makes PC games ultimately malleable: players reconfigure the game by creating new content, altering the code and changing the behaviours of the game engine. Using a semiotic framework, Sihvonen suggests a signification process that includes representation, interpretation, investigation and experimentation with the game system and rules. From its historical roots in the shoot'em up games, the author bares the fascinating evolution and dynamics of modding, where gender stereotypes, the thrills of hacking and living the Sims' American Dream intersect with the aesthetic and operational dimensions of modding.